Birth of Homo Mimeticus: Nietzsche, Genealogy, Communication. Issue 1 (April 2022) - Lawtoo, Nidesh
Abstract : This article develops a genealogical account of the birth of homo mimeticus – out of mimetic communication. While genealogy tends to be suspicious of stable origins, a key advocate of the genealogical method such as Friedrich Nietzsche was deeply interested in diagnosing the evolution of non-verbal forms of 'communication' that, in his view, gave birth to language, consciousness, and culture. For the Nietzschean mimetic theory this article proposes, mimesis is thus not simply an image far removed from reality but an all too human, embodied, and relational form of communication that makes Homo sapiens an eminently social species. I argue that Nietzsche's genealogy of the origins of language (out of mimetic reflexes) opens up a timely alternative to both the Scylla of (post)structuralist accounts of arbitrary linguistic signs and the Charybdis of speculative hypotheses on founding sacrificial murders. In the process, it may also pave the way for recent re-discoveries of the role mimesis played in the birth of that thoroughly original species we call, homo mimeticus .